Effect of zein and zein‐Peganum harmala extract coatings of eggshell on the internal quality of eggs and control of Salmonella enteritidis. Issue 10 (14th September 2022) - Entezari, Asma; Roshanak, Sahar; Shakeri, Golshan; Sedaghat, Nasser
Abstract : Abstract: The high nutritional value of egg makes it vital to the human diet. Salmonella enteritidis is one of the major global causes of foodborne enteritis in humans. The chicken intestine is the main source of S . enteritidis . Therefore, eggs play an important role in the transmission of salmonellosis. In this study, we evaluated the effectiveness of coatings made of zein either alone or in combination of hydro‐alcoholic extract of Peganum harmala on the quality of eggs and control of S. enteritidis at 7°C during a period of 28 days. Results demonstrated that both types of the coating significantly improved the physicochemical properties of eggs including weight loss, Haugh unit, and yolk index compared to controls during storage. However, neither of coatings resulted in significant changes in yolk color and pH ( p < 0.05). Both types of coating caused two log CFU/ml reductions in S. enteritidis population from the first day and eliminated the contamination at the end of the experiment (for 28 days). Salmonella elimination occurred at day 21 for zein‐plant extract coating. Our findings demonstrate zein coating can be an appropriate approach for maintaining the quality of eggs during shelf life and an effective and economic strategy for control of S. enteritidis in eggs. Practical Application: This study shows that the application of zein coating can preserve the internal quality and freshness of eggs during storage. Moreover, zein coating is a highly effective strategy in the control of Salmonella . This method can be used on a commercial scale for enhancing the safety and quality of eggs.